2016
DOI: 10.1159/000449288
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Are Administrative Data for Capturing Stroke Patients and Their Care

Abstract: Background/Aims: The reliability of diagnostic coding of acute stroke and transient ischemic attack (TIA) in administrative data is uncertain. The purpose of this study is to determine the agreement between administrative data sources and chart audit for the identification of stroke type, stroke risk factors, and the use of hospital-based diagnostic procedures in patients with stroke or TIA. Methods: Medical charts for a population-based sample of patients (n = 14,508) with ischemic stroke, intracerebral hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 25 publications
1
59
2
Order By: Relevance
“…A recent study from Ontario demonstrated that in inpatients who suffered a stroke, administrative data alone were able to identify those who had MRIs or CTs of the brain in over 90% of cases. 17 In contrast, in that study, administrative data were only able to identify transthoracic echocardiograms in approximately 40% of inpatients. 17 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A recent study from Ontario demonstrated that in inpatients who suffered a stroke, administrative data alone were able to identify those who had MRIs or CTs of the brain in over 90% of cases. 17 In contrast, in that study, administrative data were only able to identify transthoracic echocardiograms in approximately 40% of inpatients. 17 …”
Section: Discussionmentioning
confidence: 79%
“… 17 In contrast, in that study, administrative data were only able to identify transthoracic echocardiograms in approximately 40% of inpatients. 17 …”
Section: Discussionmentioning
confidence: 79%
“…These codes have been previously validated at other Canadian academic teaching hospitals and have a positive predictive value above 89%. 19 For patients with more than 1 stroke during our study's time frame, we included only the results from their first admission for stroke. Patients who received tissue plasminogen activator were excluded from our study as these patients are admitted to the intensive care unit and then admitted to a neurology service, and thus not consistently captured in the GEMINI database.…”
Section: Study Populationmentioning
confidence: 99%
“…Of the 11 (0.9%) patients who had a cardiac thrombus, 5 already had an indication for anticoagulation (most often atrial fibrillation). For the remaining 6 patients, 5 were Prior stroke or TIA 243 (19) 139 24Diabetes mellitus 340 (27) 149 (25) Coronary artery disease 128 (10) 60 (10) Heart failure 73 626 4Antiplatelet use 396 (31) 215 (36) Anticoagulant use 141 (11) 75 (13) Note: SD = standard deviation, TIA = transient ischemic attack. *Unless stated otherwise.…”
Section: Echocardiographic Findingsmentioning
confidence: 99%
See 1 more Smart Citation